2021
DOI: 10.3390/ijms222312889
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Biological Activity, New Formulations and Prodrugs of Ferulic Acid

Abstract: Trans-ferulic acid (FA) is a derivative of 4-hydroxycinnamic acid, which is found in many food products, fruits and beverages. It has scientifically proven antioxidant, anti-inflammatory and antibacterial properties. However, its low ability to permeate through biological barriers (e.g., the blood–brain barrier, BBB), its low bioavailability and its fast elimination from the gastrointestinal tract after oral administration limit its clinical use, e.g., for the treatment of neurodegenerative diseases, such as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 107 publications
0
32
0
1
Order By: Relevance
“…Acting as an antioxidant, FA can inhibit the enzymes that lead to ROS formation, scavenge free radicals, and promote the antioxidant enzymes activity [ 372 ]. This makes FA a compound widely used in cosmetics and in food industry, especially as an anti-aging agent [ 377 ]. It has been demonstrated to protect skin from UV radiation through its capacity to reduce the activity of the stress-inducible protein Gadd45 α, the expression of MMP-1 and MMP-3 mRNAs, as well as enhancing the levels of the antioxidant enzymes SOD1 and CAT [ 326 , 378 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acting as an antioxidant, FA can inhibit the enzymes that lead to ROS formation, scavenge free radicals, and promote the antioxidant enzymes activity [ 372 ]. This makes FA a compound widely used in cosmetics and in food industry, especially as an anti-aging agent [ 377 ]. It has been demonstrated to protect skin from UV radiation through its capacity to reduce the activity of the stress-inducible protein Gadd45 α, the expression of MMP-1 and MMP-3 mRNAs, as well as enhancing the levels of the antioxidant enzymes SOD1 and CAT [ 326 , 378 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ferulic acid (FA), a hydroxycinnamic acid that is widely present in plant cell walls, has anti-microbial, antioxidant, and anti-inflammatory properties ( Stompor-Goracy and Machaczka, 2021 ). Mir et al (2018) demonstrated that FA suppressed inflammatory cytokines, increased antioxidant levels, and thus attenuated fibrosis and improved renal function in mice with LPS-induced AKI mediated by the NF-κB signaling pathway.…”
Section: Therapeutic Approaches In Sepsis-induced Acute Kidney Injurymentioning
confidence: 99%
“…Many research findings have shown that FA plays an essential role as an antiinflammatory agent, suppressing the production of pro-inflammatory cytokines, promoting the production of anti-inflammatory cytokines, and increasing the expression of stress-responsive genes and antioxidant molecules like metallothioneins [19]. Moreover, this natural acid's anticancer effect is linked to its capacity to decrease reactive oxygen species, which shields cellular components from oxidative damage [20]. Furthermore, FA treatment of diabetic rats was observed to restore normal blood glucose and insulin levels [19].…”
Section: Introductionmentioning
confidence: 99%